Literature Review On Future Technology Trends In User Interface Development In Human Computer Interaction - Fatwa Aulia; Nouval Khairi; M. Khalil Gibran (Jurnal Kendali Teknik dan Sains, 2025)
The continuous evolution of technology has significantly transformed the way humans interact with computers, moving beyond traditional keyboard and mouse inputs toward more natural and adaptive interfaces. This literature review examines the current and emerging trends in user interface (UI) development within the context of Human-Computer Interaction (HCI), with a specific focus on future-oriented innovations. Key areas of discussion include voice-user interfaces (VUIs), gesture-based interaction systems, adaptive and context-aware UIs, artificial intelligence (AI) integration, and neuroadaptive technologies. The study employs a qualitative analysis method, drawing upon scholarly publications from 2020 to 2025 and emphasizing the contributions of researchers from Universitas Islam Negeri Sumatera Utara, particularly M. Khalil Gibran. These technologies are assessed for their usability, accessibility, efficiency, and their ability to enhance user satisfaction through personalization and contextual awareness. Results from reviewed studies suggest that adaptive and AI-driven UIs are becoming essential in delivering personalized user experiences